2010
DOI: 10.7589/0090-3558-46.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Hematology, Serum Chemistry, and Body Mass of Free-Ranging and Captive Canada Lynx in Minnesota

Abstract: ABSTRACT:Baseline blood chemistry data could be particularly valuable if reference values from free-ranging populations of rare or endangered species are not available. The Canada lynx (Lynx canadensis) is listed as threatened under the Endangered Species Act in the conterminous United States, even though the species is managed as a furbearer in Alaska and in most provinces of Canada. Body mass, blood chemistry, and hematologic data for free-ranging lynx were collected from 2003 to 2007 and for captive lynx fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…These findings are consistent with findings of a previous study of Canada lynx where they found males were heavier than females [4] . The difference in weights between males and females could be explained by high androgen levels in males.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are consistent with findings of a previous study of Canada lynx where they found males were heavier than females [4] . The difference in weights between males and females could be explained by high androgen levels in males.…”
Section: Discussionsupporting
confidence: 83%
“…Further, they can be very useful in monitoring prognosis following treatment. However, there are few baseline haematologic and serum chemistry values for small free-ranging felids in the literature, which means that, at present, domestic cats values are used as a reference [4] . This is in spite of the fact that the values might not be similar in different felid species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, for 17 of the 38 wild cat species blood profiles have been obtained and described in scientific literature (Akuzawa, Mochizuki, & Yasuda, ; Brown, Lappin, Brown, Munkhtsog, & Swanson, ; Caro et al., ; Dunbar, Nol, & Linda, ; Erasmus, ; Kocan, Blouin, & Glenn, ; Marco, Martinez, Pastor, & Lavin, ; Prihirunkit, Salakij, Apibal, & Narkkong, ; Salakij, Salakij, Narkkong, Sirinarumitr, & Pattanarangsan, ,b, b, , , and others). However, blood profiles can be influenced significantly by the sampling procedure, including capture method, type of anesthesia, and time to blood collection (Moen, Rasmussen, Burdett, & Pelican, ; Serieys et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Capturing wild cats is a labor‐consuming procedure, not standardized, and may include trapping, chasing, capturing with the nets, darting with anesthetic drugs and other methods depending on cat species and study place (in the wild or captivity) (Beltrán, Delibes, Recio, & Aza, ; Caro et al., ; Dunbar et al., ; Naidenko, Pavlova, & Kirilyuk, , ; Salakij, Salakij, Prihirunkit, Narkkong, & Pitakkingthong, ). The common procedure of collecting blood samples (handling time) in wild cats can be extremely stressful and implies the immobilization of animals with capture and anesthesia up to an hour both in captivity and in the wild (Akuzawa et al., ; Brown et al., ; Marco et al., ; Moen et al., ). Nevertheless, it is known that the basal glucocorticoid level must be sampled within 3 min of capture in birds and reptiles, after that, it increases dramatically (Loshchagina, Tsvey, & Naidenko, ; Romero & Reed, ).…”
Section: Introductionmentioning
confidence: 99%